PEDERSEN DIFFICULTY INDEX ACCURATELY PREDICTS OPERATIVE DURATION IN MANDIBULAR THIRD MOLAR REMOVAL: A CROSS-SECTIONAL CLINICAL STUDY - Prestya, Pebrian Diki; Yuza, Abel Tasman; Zam, Syarifah Nova Amiza (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Mandibular third molar removal is one of the most performed procedures in oral surgery. Surgical intervention is indicated for both preventive and therapeutic purposes. Preoperative evaluation of surgical difficulty is a critical determinant in the management of impacted mandibular third molars. There are methods for predicting extraction complexity, including the widely recognized Pedersen Difficulty Index, which provides a systematic approach to assessing surgical risk and procedural. The aim of this study understanding the correlation between Pedersen Difficulty Index as a predictor of operative duration in Mandibular Third Molar Removal at Department of OMFS Unimus Dental Teaching Hospital. Design of this study is analytics observational with a cross-sectional study at Department of Oral and Maxillofacial Surgery in January 2026 — March 2026. Minimum sample size was estimated for correlation analysis using a 95% confidence level. Data obtained from 29 patients undergo third molar removal. Variables in this study was Pedersen Difficulty Index and duration in Mandibular third molar removal. Sampling was conducted using consecutive sampling. Data analysis using Spearman rank correlation test. Results: Statistically highly significant difference in duration was observed among three levels of difficulty index (p=0.000; p<0.05). A Spearman’s Rank correlation coefficient of 0.733 indicates a strong positive correlation between the Pedersen difficulty score and operative duration. There is a strong and statistically significant positive correlation between the Pedersen difficulty index and duration in impacted mandibular third molar removal. Higher difficulty scores associated with longer surgical times, indicating that the Pedersen Difficulty Index is a reliable predictor of complexity.